Biodegradable Packaging Made from Proteins - Samar Sahraee; Jafar Milani (مجله پژوهش‌های علوم و صنایع غذایی ایران)
Protein films have gained significant attention in the development of sustainable packaging materials due to their exceptional properties and versatility. These films offer superior gas barrier properties, specific mechanical characteristics, and enhanced intermolecular connection capabilities compared to other biopolymers. Researchers are exploring innovative methods to enhance the film-forming properties of proteins, improve their mechanical strength, and optimize their gas barrier performance. Various protein sources, such as gelatin, whey protein, soy protein, corn zein, wheat gluten, and casein, are being investigated for film fabrication. Techniques to modify protein films, including the incorporation of additives, crosslinking agents, and nanomaterials, are being explored to enhance their properties. The development of protein-based composite films, by blending proteins with other biopolymers or synthetic materials, is also being explored to achieve improved performance and functionality. Advancements in processing technologies, such as film casting, extrusion, and electrospinning, enable precise control over the thickness, morphology, and structural properties of protein films. These films not only offer enhanced barrier properties but also possess biodegradability and renewable characteristics, aligning with the increasing demand for eco-friendly packaging solutions. The preparation and improvement of protein films hold significant potential for revolutionizing the packaging industry and contributing to a greener and more environmentally friendly future. This review provides an overview of current research and advancements in the field, addressing various protein sources, film modification techniques, processing methods, challenges, and future prospects.